The Impurity of Stone Vessels in 11QTa and CD in Light of the Chalk Vessel Finds at Kh. Qumran - Adler, Yonatan (Dead Sea discoveries, 2020)
Scholars have argued that 11QTa and CD view stone vessels as susceptible to impurity. Chalk vessel finds at Kh. Qumran have presented a challenge to this idea, and solutions to date have been unsatisfying. The recent publication of final reports on these finds invites us to reconsider both the archaeological and textual evidence relating to the ritual status of stone vessels at Qumran. The typological profile of the Kh. Qumran assemblage parallels that found at Jewish sites elsewhere. It will be argued that both 11QTa and CD viewed stone vessels as unsusceptible to most kinds of ritual impurity—apart from corpse impurity. The pentateuchal basis for this understanding will be elucidated, and it will be argued that the position of 11QTa and CD on the matter was common among contemporary Jews. The foregoing will allow an investigation into the origins of the chalk vessel industry in the late 1st century BCE.